Homeostasis Revisited: Patterns of Stability and Rebalancing in Older Adults' Social Lives. (21st February 2020) - Cornwell, Benjamin; Goldman, Alyssa; Laumann, Edward O
Abstract: Objectives: To examine patterns of change in later-life social connectedness: (a) the extent and direction of changes in different aspects of social connectedness, including size, density, and composition of social networks, network turnover, and three types of community involvement and (b) the sequential nature of these changes over time. Method: We use three waves of nationally representative data from the National Social Life, Health, and Aging Project, collected from 2005/2006 to 2015/2016. Respondents were between the ages of 67 and 95 at follow-up. Types of changes in their social connectedness between the two successive 5-year periods are compared to discern over-time change patterns. Results: Analyses reveal stability or growth in the sizes of most older adults' social networks, their access to non-kin ties, network expansiveness, as well as several forms of community involvement. Most older adults experienced turnover within their networks, but losses and additions usually offset each other, resulting in generally stable network size and structural features. Moreover, when older adults reported decreases (increases) in a given form of social connectedness during the first half of the study period, these changes were typically followed by countervailing increases (decreases) over the subsequent 5-year period. This general pattern holds for both network and community connectedness. Discussion: There is an overwhelming tendency toward either maintaining or rebalancing previous structures and levels of both personal network connectedness and community involvement. This results in overall homeostasis. We close by discussing the need for a unifying theoretical framework that can explain these patterns.